2010
DOI: 10.1128/aem.02692-09
|View full text |Cite
|
Sign up to set email alerts
|

High Abundance of Ammonia-OxidizingArchaeain Coastal Waters, Determined Using a Modified DNA Extraction Method

Abstract: . Appropriate controls to verify this basic assumption are rarely included. Here three different DNA extractions, performed with two commercial kits (FastDNA and UltraClean) and a standard phenol-chloroform method, and two alternative filtration methods (Sterivex and 25-mm-diameter polycarbonate filters) were evaluated, using the addition of Nitrosopumilus maritimus cells to track the recovery of DNA from marine Archaea. After the comparison, a simplified phenol-chloroform extraction method was developed and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 47 publications
3
107
0
2
Order By: Relevance
“…These distinctive differences are directly relevant to their possible contribution to nitrification in different marine environments-including lower salinity coastal regions, the photic zone of the upper water column, and the increasing acidification of ocean waters associated with climate change. (8,38,39). Predominance of AOA was consistent with generally submicromolar concentrations of ammonia at these stations, sufficient to support AOA such as SCM1 but not known AOB (24).…”
Section: Significancementioning
confidence: 62%
“…These distinctive differences are directly relevant to their possible contribution to nitrification in different marine environments-including lower salinity coastal regions, the photic zone of the upper water column, and the increasing acidification of ocean waters associated with climate change. (8,38,39). Predominance of AOA was consistent with generally submicromolar concentrations of ammonia at these stations, sufficient to support AOA such as SCM1 but not known AOB (24).…”
Section: Significancementioning
confidence: 62%
“…We quantified Thaumarchaeota via qPCR and performed direct cell counts to quantify total prokaryotes as previously described (43,44,54). DNA for 16S rRNA sequencing was extracted, amplified, and sequenced as described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…We combined bacterial 16S rRNA gene sequence-derived phylogenetic data with current knowledge of corrin biosynthesis genes (including our analysis) across different phylogenetic groups to infer the cobalamin biosynthetic capacity of organisms in the microbial communities at our study site as likely, unknown, or unlikely (Table S3). We quantified Thaumarchaeota by quantitative PCR (qPCR) (43,44) and calculated their contribution to the microbial population by comparing this value to direct counts of prokaryotic cells determined for each sample. Our analysis at five targeted locations in the North Pacific suggested that Thaumarchaeota represent 30-80% of prokaryotes having likely or unknown genetic capacity to synthesize cobalamin in the lower euphotic zone and deeper ( Fig.…”
Section: All Of the 49mentioning
confidence: 99%
“…(21) This extraction method may have an inherent bias toward the extraction of Bacterial DNA over Archaeal DNA. (22) …”
Section: Microbial Sampling and Dna Extractionmentioning
confidence: 99%